Analisis Faktor-Faktor yang mempengaruhi Indeks Pembangunan Manusia (IPM) di Sumatera Utara - Mulya Syahputra Daulay; Alfi Maulani (Journal of Mathematics Theory and Applications, 2025)
The Human Development Index (HDI) measures human development achievements based on a number of basic components of quality of life. The research aims to see the influence of Expected Years of Schooling, Per Capita Expenditure and Percentage of Poor Population on the Human Development Index in North Sumatra Province. The method used in this research is a quantitative method, where the research results are then processed and analyzed to draw conclusions. From several tests, the Random Effect model (REM) was chosen as the best model. The results of the simultaneous test (F-test) of all X variables have an influence on Y variable because the F_count (714.6759) > F_table (3.30) and the test results are proven by a significant value of 0.0000 <0.05, it is concluded that H_1 is accepted and H_0 is rejected. The long-school expectation variable (HLS) (x_1) partially influences HDI in North Sumatra Province because it has a significant value of 0.0000 <0.05 and the value of T_count (15.47633) > T_table (2.039613). The variable per capita expenditure (PP) (x_2) partially influences HDI in North Sumatra Province because it has a significant value of 0.000 <0.05 and the value of T_count (23.32513) > T_table (2.039613). The variable percentage of poor people (PPM) (x_3) partially infuences HDI in North Sumatra Province because it has a significant value of 0.0000 <0.05 and the value of T_count (-4.117351) < T_table (-2.039613).